Cardiac Limited Ultrasound Examination Techniques to Augment the Bedside Cardiac Physical Examination. (12th August 2015) - Kimura, Bruce J.; Shaw, David J.; Amundson, Stan A.; Phan, James N.; Blanchard, Daniel G.; DeMaria, Anthony N.
Abstract : The current practice of physical diagnosis is dependent on physician skills and biases, inductive reasoning, and time efficiency. Although the clinical utility of echocardiography is well known, few data exist on how to integrate 2‐dimensional screening "quick‐look" ultrasound applications into a novel, modernized cardiac physical examination. We discuss the evidence basis behind ultrasound "signs" pertinent to the cardiovascular system and elemental in synthesis of bedside diagnoses and propose the application of a brief cardiac limited ultrasound examination based on these signs. An ultrasound‐augmented cardiac physical examination can be taught in traditional medical education and has the potential to improve bedside diagnosis and patient care.